2015
DOI: 10.7705/biomedica.v35i4.2572
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii resistente a carbapenémicos causando osteomielitis e infecciones en piel y tejidos blandos en hospitales de Medellín, Colombia

Abstract: : diseño y experimentos Todos los autores participaron en la recolección de datos, el análisis de la información y en la elaboración del manuscrito.Acinetobacter baumannii resistente a carbapenémicos causante de osteomielitis e infecciones de la piel y los tejidos blandos en hospitales de Medellín, Colombia Introducción. Acinetobacter baumannii es una bacteria oportunista que infecta a pacientes gravemente enfermos, principalmente con neumonía asociada al uso del respirador y bacteriemia. La aparición de resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…This MLST has been identified previously in Mexican hospitals and in other countries of Latin America [17][18][19]. The MLST758 is an understudied lineage that does not belong to the international clones I and II; it has spread to Canada, Mexico, Honduras, and Colombia.…”
Section: Plos Onementioning
confidence: 71%
“…This MLST has been identified previously in Mexican hospitals and in other countries of Latin America [17][18][19]. The MLST758 is an understudied lineage that does not belong to the international clones I and II; it has spread to Canada, Mexico, Honduras, and Colombia.…”
Section: Plos Onementioning
confidence: 71%
“…2). According to the PubMLST database, several studies have reported isolates from this ST in Canada (24), Mexico and Honduras (19,23), and even Colombia (25). Of note, ST758 and ST1091 correspond to ST156 under the MLST Pasteur scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, ST758 and ST1091 correspond to ST156 under the MLST Pasteur scheme. Then, given that previous publications considering Latin American isolates (20,25,26) have used the MLST Pasteur scheme, we constructed an eBURST diagram using the Pasteur scheme, and a partial view highlighting ST156 is shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown a decrease in the frequency of resistant A. baumannii isolates in comparison with other multidrug-resistant Gram-negative bacilli causing infection in Colombia and particularly in Medellín [21, 49]. Likewise, a surveillance study conducted by our research group in five hospitals of Medellin, included only 32 carbapenem-resistant isolates during two years of study, showing the low frequency of this bacteria in our city [50]. …”
Section: Discussionmentioning
confidence: 85%